Enhancing Waqf Accountability: Nazhir’s Perspective towards Waqf Reporting - Monica, Sandra; Mukhlisin, Murniati; Fatah, Dede Abdul (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2020)
This study explores the best reporting form as a representation of waqf accountability through nazhir’s perspectives, i.e. waqf institutions in Indonesia. The method used in this study is the Analytic Network Process combined with Delphi. The results show that financial statements obtained from the first rank as the best reporting form. However, the waqf institutions could have difficulties in delivering a high-quality financial statement since there is a lack of understanding about the new waqf accounting standard that will be applied in 2021. The development of a comprehensive and down to earth guidance is crucial in helping the institutions apply the standard, with a help line as a backup. Continuous education and certification are also useful to enhance the skills of human resources in the waqf institutions concerning waqf management and accountability reporting. AbstrakPenelitian ini bertujuan untuk mengksplorasi bentuk pelaporan terbaik sebagai representasi akuntabilitas wakaf, dilihat dari perspektif nazhir, yang dalam hal ini adalah institusi wakaf di Indonesia. Metode yang digunakan adalah Analytic Network Process yang dikombinasikan dengan Delphi. Hasil penelitian ini menyimpulkan bahwa laporan keuangan yang diperoleh dari tingkat pertama adalah bentuk pelaporan terbaik. Akan tetapi, pemahaman institusi wakaf terhadap standar akuntansi wakaf terbaru yang akan diberlakukan pada tahun 2021 masih sangat kurang. Ini menyebabkan institusi wakaf mengalami kesulitan dalam menyusun laporan keuangan yang berkualitas baik. Pengembangan pedoman pelaporan yang komprehensif dan mudah dipahami diperlukan untuk membantu institusi wakaf. Hal ini perlu disertai layanan bantuan yang dapat diakses setiap saat. Pendidikan berkelanjutan dan sertifikasi juga dibutuhkan untuk meningkatkan keahlian sumber daya manusia di institusi wakaf terkait manajemen wakaf dan pelaporan akuntabilitas.